Strategi Pembelajaran Guna Meningkatkan Kualitas Belajar Siswa Melalui Sarana Prasarana di SDIT Al Fatih Depok - Nurkaidah; Dede Rosyada (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
A Strategy is a method or approach that includes all methods or approaches that are closely related to the implementation of concepts or plans and activities within a certain period of time. Facilities and infrastructure are needed to support the smooth running of activities in the learning process, so each school must manage the facilities and infrastructure it has. This research intends to explain three things: (1) SDIT al Fatih Depok's strategy in improving learning standards; (2) Al Fatih SDIT planning to improve the standards of facilities and infrastructure; and (3) The role of teachers in improving learning standards at SDIT Al Fatih Depok through facilities and infrastructure. In this study, observational studies and literature reviews were combined with qualitative methodology. In-depth interviews, documentation studies, and participant observation were the three data collection methods used. It can be concluded that the Strategy for Improving the Quality of Learning through Improving Facilities and Infrastructure has succeeded in helping students achieve better learning outcomes based on the quality of teaching provided by teachers at SDIT Al Fatih Depok.